The Impact of an Incidental Dose on Axillary Tumor Control and Toxicity in Localized Breast Cancer: A Retrospective Analysis - Schmitt, Martin; Chambrelant, Isabelle; Hong Chheang, Parigna; Pflumio, Carole; Hild, Carole; Petit, Thierry; Noël, Georges (Cancers, 2022)
Purpose: The dosimetric analysis of the incidental axillary dose delivered to axillary lymph node levels I–III by different techniques of whole breast irradiation and the analysis of prognostic factors of axillary recurrence of breast cancer. Methods: We perform a retrospective analysis that includes 171 patients with localized breast carcinoma irradiated at Centre Paul Strauss. To be included in the study, patients had to have a histological confirmation of breast cancer diagnosis, surgical treatment without axillary lymph node dissection (ALND), whole breast irradiation without axillary irradiation by a specific field, and a treatment plan available. Results: Three patients had lymph node recurrence. There was no significant correlation between the maximal or mean dose delivered at the three axillary levels and the risk of axillary lymph node recurrence. There was no significant correlation between the irradiation technique and the risk of axillary lymph node recurrence. Two patients, both in the HT group, had lymphoedema. There was significantly more lymphoedema in the HT group than in the ST and IMRT groups (p < 0.048). The mean dose in level II was significantly higher in the group of patients with lymphoedema (3.45 Gy (1.08; 9.62) vs. 23.4 Gy (23.1; 23.6)) (p < 0.02). Conclusion: The irradiation technique has an influence on the incidental dose delivered to the axillary area, but has no influence on the risk of axillary recurrence. The risk of lymphoedema could be related to the use of HT and the mean dose delivered at level II.